2019
DOI: 10.3390/jcm8070930
|View full text |Cite
|
Sign up to set email alerts
|

The Bruxoff Device as a Screening Method for Sleep Bruxism in Dental Practice

Abstract: Sleep bruxism (SB) is a masticatory muscle activity during sleep and a common phenomenon. Severe SB can have a serious impact on the success of dental treatment. Reliable methods of screening and diagnosing patients with SB are crucial. Therefore, in this study, a Bruxoff device as a potential screening and diagnostic method for sleep bruxism was evaluated. A total of 60 adults participated in this study: 35 patients with symptoms of bruxism (study group) and 25 asymptomatic patients (control group). Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 74 publications
1
23
0
2
Order By: Relevance
“…The present study showed the statistically significant correlation between the PSS-10 score and Bruxism Index, evaluated using the Bruxoff device. According to previous studies, Bruxoff sensitivity is estimated at 92–100%, whereas its specificity ranges from 76% to 91.6% [29,35,36], showing high reliability of the device in diagnosing bruxism. The results of the present study emphasized the notion that the higher perceived stress score, the higher the Bruxism Index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed the statistically significant correlation between the PSS-10 score and Bruxism Index, evaluated using the Bruxoff device. According to previous studies, Bruxoff sensitivity is estimated at 92–100%, whereas its specificity ranges from 76% to 91.6% [29,35,36], showing high reliability of the device in diagnosing bruxism. The results of the present study emphasized the notion that the higher perceived stress score, the higher the Bruxism Index.…”
Section: Discussionmentioning
confidence: 99%
“…Masseter and temporal muscles were examined, both the origins and heads of the muscles, for signs of pain. In addition, the study used a portable electromyography/electrocardiogram (EMG/ECG) device (Bruxoff, Bioelettronica, Turin, Italy), according to the protocol described by Saczuk et al [29], to evaluate the overnight Bruxism Index (number of bruxism episodes per hour) in both groups. Based on the examination, participants were divided into study and control groups.…”
Section: Methodsmentioning
confidence: 99%
“…Stres merupakan salah satu faktor yang dapat memicu terjadinya bruxism pada wanita. 27 Hasil analisis pada penelitian ini menunjukan bahwa selisih ketinggian tulang kortikal mandibula pada penderita dan bukan penderita bruxism hanya sebesar 0,0184mm pada regio kanan dan 0,0125mm pada regio kiri dimana secara statistik tidak terdapat perbedaan yang signifikan. Keterbatasan pada penelitian ini yaitu dilakukan dengan menggunakan data sekunder sehingga data pasien yang didapat terbatas, seperti lamanya pasien menderita bruxism, kebiasaan buruk pasien lainnya, dan tingkat keparahan dari bruxism yang diderita.…”
Section: Pembahasanunclassified
“…The work discovered 16.8% wide inequality and inadequate diagnosis, and 21.9% of applicants planned cognitive-behavioral treatment. Saczuk et al [26] evaluated the screening and detection method of bruxism. The researchers used the total number of sixty adults, including twenty-five healthy and thirty-five with bruxism.…”
Section: Introductionmentioning
confidence: 99%